‘Magnetic Virtue’: Academic Alba Amicorum in the Dutch Republic, 1575-1750 - Llano, Manuel (Early Modern Low Countries, 2022)
While autograph alba originally appeared as memorabilia of student life, it is often argued that the possibility of boosting their owner’s reputation by association with leading scholars led to their careerist exploitation during the seventeenth century. In German universities, aspiring academics would seek out the most renowned luminaries in the world of learning, and even established scholars would on occasion keep an album with signatures of eminent peers. This article assesses the influence of this practice in Dutch universities and considers whether a careerist use of autograph alba existed in the Dutch Republic, through an exploration of some quantitative trends in the Dutch National Library’s (KB) inventory of autograph alba and the union catalogue Repertorium Alborum Amicorum (RAA).